Resource accumulation for opportunity identification and exploitation by lead academic and non-academic entrepreneurs - Farquharson, Maris Hunter (2009)
Understanding the opportunity identification process represents a core entrepreneurship domain research focus. Many studies focusing on traditional firm performance outcomes neglect the entrepreneurial human and social capital drivers that are linked to opportunity identification. Research on Higher Education Institutes (HEIs) has explored different dynamics associated with the formation of firms emanating from HEIs (e.g. from the perspective of the individual firm; by exploring support and influence offered by the parent organisation; and through analysis of the spinout process). The contribution from the individual entrepreneur in identifying an opportunity for commercialisation has not been fully explored.